Organizational Commitment and Organizational Citizenship Behavior of Female Employees - Sudiyani, Ni Nyoman; Herlambang, Putu Gede Denny; Goca, I Gusti Putu Agung Widya (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The purpose of this study is to examine how female employees' organizational citizenship behavior (OCB) is impacted by organizational commitment (affective, normative, and continuance commitment). With a sample of 108 female respondents, this study was carried out at the Tabanan Regency Village Credit Institution (LPD). Purposive sampling was used in order to determine the sample. Structural Equation Modeling (SEM) - Partial Least Square (PLS) with WARP-PLS.6 software was used to analyze the data. The findings demonstrated that OCB is positively and significantly impacted by organizational commitment, which is made up of emotional, normative, and continuity commitments. According to the study's findings, normative commitment significantly affects OCB. The significance of OCB in the conventional framework is addressed in order to understand the theoretical and practical ramifications of these linkages.